SPATIO-TEMPORAL ASSESSMENT OF INFANT MORTALITY IN GOMBE METROPOLIS GOMBE STATE, NIGERIA - YAYAJI AHMED, BILKISU; MUHAMMED BASHIR , BELLO; MYLON, ISTIFANUS (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Infant mortality refers to the number of deaths of infant under one year of age per 1000 live birth in a given population. It is an important indicator of the overall health and well-being of a society, reflecting factors such as access to healthcare, nutrition, sanitation and socio-economic conditions. This study has the following objectives; mapping-out the spatial distribution of infant mortality cases, assess the temporal variation of infant mortality and identify the gender with the highest infant mortality rate. Primary data GPS Point and interviews and secondary data Hospital records were used for the achievement of the aim and objectives of the study. Simple descriptive statistical methods and ArcGIS 2019 software were employed in the analysis of the data collected. The research found out that the infant mortality is highest among the male gender with 57% then followed by female with 43%, this is because the male gender is biologically weaker and more susceptible to disease and premature death than the female. Major causes of infant mortality found by the study are; low birth weight respiratory failure, apnea attack, pneumonia, sepsis, meningitis, severe birth asphyxia, Septembers is, burn injury, measles, and dehydration. The area with the highest number of infant mortality is Tudun-wada with (567), followed by Bogo (523), then Gabukka (434). The factors that contributed to high infant mortality in the areas includes environmental factors i.e. location of the areas in the Slum and. Infant mortality was highest in the years 2014 (599) followed by year 2015 (593) and (571) recorded in 2016. The study concluded that infant mortality is decreasing due to improvement in health conditions and efforts made by government at all levels as well as the support and intervention from partners. There is need for effective allocation of funds by the Federal, State and LGA to strengthen community health care centres and increase programmes to create awareness.